(untitled) (Global Journal of Science Frontier Research, 2012)
During 2009 Rabi season flood of river Krishna, the cultivated area of 128 Km2 was flooded in the northern part of Karnataka catchment. The flood entirely killed the vegetations stands on the fields. After wards, the effects of the flood on the ecological properties of the soils and the conditions of agricultural production had been evaluated. A study was conducted to estimate the flood effects on heavy metals concentrations and on the nutrient status of the soils. The sediment layer left from the flood had a thickness of several mm. Boron, Molybdenum within this layer were in between proscribed values and the metal ions concentrations of Iron, Zinc , Copper, were found slightly above the prescribed limits. Thus no restriction had to be announced for food production purposes. Regarding the Major and Secondary nutrients status of the flooded soils, only the mineral Nitrogen content was substantially reduced when compared to not flooded soils. This effect could most probably be related to denitrification processes as a result of anaerobic conditions during the flood. Available Potash (K2O) and Phosphorus (P2O5) found more than the prescribed limits.